Students learning engagement in the flipped classroom: Systematic literature review - Ridha, Muhammad; Rahman, Faisal; Islamy, Muhammad Irfan (Jurnal Inovasi Teknologi Pendidikan, 2024)
The flipped classroom offers greater flexibility and meaningfulness in learning activities. Students have more space and time to construct their knowledge and skills freely. However, the presence of students in learning activities does not necessarily guarantee that students are actively engaged in creating their expertise and skills. This study conducts a systematic literature review to investigate effective strategies to ensure students' learning engagement in flipped classrooms and factors that hinder students' learning engagement. It was performed following the Kitchenman and Charter's rules and strategies. The review covered 47 articles that were published between 2018-2023. The significant findings indicated that effective strategies used to ensure and enhance students' learning engagement in the flipped classroom are gamification, providing immediate feedback, timely guidance, working in groups, scaffolding, peer coaching, user-friendly technology, learning videos with a short duration, assignments before in-class session, reflective-thinking strategy, self-regulated learning, and guided questions. Additionally, supporting materials for pre-class sessions, working in groups with the same students, doing the same activities repeatedly, low level of self-regulation, long duration and low quality of learning videos, students' perception toward the roles of the lecturer and lecturer's communicative skills can hinder students from engaging in learning activities. Therefore, when implementing a flipped classroom, the lecturers should facilitate and ignite students' learning needs and interests. Moreover, using user-friendly digital technology is essential to create an atmosphere that encourages students' engagement either in pre-class, in-class, or after-class.